Isolation and Identification of Bacterial Causes of Acute Tonsillitis - Frial Gemeel Abd (Journal of Global Pharma Technology, 2018)
Acute tonsillitis was an inflammatory process of the tonsillar tissues and was usually infectious in nature. Acute tonsillitis starts suddenly and usually goes away again within one to two weeks. This infection was often bacterial, or sometimes viral.   A hundred of blood and swabs specimens were collected from patients who were suffering from tonsillitis whose did not take any drugs for both sex with age ranging from 1-60 years in AL-Hilla-Teaching hospital and hospital Babylon for birth and children during a period from October 2017 through January 2018 . The causative agent for tonsillitis was   isolated and diagnostic of microorganism according to morphological and biochemical test  by using VITEK compact 2 .The results  appeared the number of gram positive bacteria about 100 and 23 isolate from  gram negative bacteria .The most common causative agent was Streptococcus pyogenes and Staphylococcus aureus. The sensitivity of bacterial to antibiotic was appeared most of bacterial resistance to amoxicillin, Cefotaxime and Aztreonam) but sensitive to other antibiotic such as Gentamycin, Chloramphenicol and Ciprofloxacin kit. Qualitative and semi quantitative ASO determination was done using the ASO latex agglutination kit. 24%of patient was ASO positive and 67% was ASO negative The level of ASO in patients that tested positive for the presence of ASO ranged from 1600IU/ml to 25600IU/ml. 12 sample were the highest concentration of 25600IU/ml .The conclusion of this study found that Streptococcus pyogenes was most common causative agent for tonsillitis and the bacteria resist amoxicillin.Keywords: Tonsillitis, Amoxicillin, Streptococcus, ASO.